Potensi Cendawan Mikoriza Arbuskular sebagai Media Pengendalian Penyakit Busuk Pelepah pada Jagung - Soenartiningsih Soenartiningsih (Puslitbang Tanaman Pangan, 2013)
Sheath blight is soil borne disease caused by Rhizoctonia solani, an important disease in maize. It could cause 100% yield loss on susceptible varieties. R. solani infects lower sheath, spreading upward to the ear, causing ear rot. Symbiosis of arbuscular mycorrhizal fungi (AMF) and maize, in addition to improving growth of plant by increasing the absorption of nutrients, especially P, was reported that the fungus was capable of inhibiting the growth of soil borne pathogens. Inhibition or control of soil borne pathogen was probably due to the increase of fenol, to stimulate the formation of flavonoids which increase the activation of phenyl alanine ammonium lyase (PAL) enzyme. Increasing flavonoid structure, however, was not directly involved in plant resistance, but it serves to synthesize chitinase and phenyl alanine ammonium lyase enzyme, which induces plant resistance. The association between AMF and maize was also causing the occurrence of lignified of the roots so that the plant was forming a physical barrier to the entry of pathogens. The development of disease caused by R. solani on the mycorrhizal roots was relatively lower compared with that of uninfected mycorrhiza. The AMF decreased the intensity of sheath blight disease up to 41% based on research conducted in the greenhouse. The AM fungi trial in the field was able to suppress sheath blight disease by 36% when in symbiotic growth with Glomus sp, while symbiosis with Acaulospora mellea suppresses the disease up to 28%.